(untitled) (World Economics and Finance Bulletin, 2023)
This article delves into the realm of digital deposit services offered by commercial banks, investigating the range of account options available to customers in the rapidly evolving digital landscape. The study employs a comprehensive approach, including a literature review, an examination of methods employed by banks, and an analysis of results to provide insights into the current state of digital deposit services. The article concludes with discussions on the implications of these findings and offers suggestions for the future enhancement of digital banking services.